The impact of high-frequency rTMS treatment on brain activity in PSCI patients: a TMS-EEG study - Xinxin Song; Jianming Fu; Yunhai Yao; Yuhong Shu; Zhongli Wang; Xuting Chen; Lianjie Ma; Fang Shen; Xiaolin Sun; Xiaoqing Ma; Ting Zhang; Rujue Jin; et al. (Frontiers in Neurology)
ObjectivesThis study employed Transcranial Magnetic Stimulation combined with Electroencephalography (TMS-EEG) to examine the impacts of high-frequency repetitive transcranial magnetic stimulation (rTMS) on brain activity and cognitive function in patients with post-stroke cognitive impairment (PSCI), focusing on changes in connectivity of the left dorsolateral prefrontal cortex (DLPFC) across different frequency bands.MethodsTwenty subacute PSCI patients were recruited for a 20-day rTMS treatment, consisting of 10 days of sham stimulation followed by 10 days of actual stimulation. Clinical function scale data and TMS-EEG data were collected before treatment (Pre), after sham stimulation (Sham), and after rTMS treatment (TMS) to analyze transcranial magnetic stimulation evoked potentials (TEP), time-frequency, and functional connectivity. Additionally, a post hoc subgroup analysis was conducted to assess the impact of education level, time since onset, and lesion size on cognitive score improvement.ResultsCompared to the Pre and Sham conditions, cognitive function and daily living ability scores significantly improved post-rTMS. Although the TEP patterns in the Pre and Sham conditions were similar, rTMS enhanced the early TEP amplitude in the left DLPFC, slowed gamma oscillations, increased connectivity in the theta and alpha bands in the bilateral DLPFC, and altered the connectivity patterns between the left DLPFC and other brain regions. Changes in theta-band wPLI were significantly positively correlated with improvements in MMSE scores (r = 0.465, p = 0.039) and MoCA scores (r = 0.493, p = 0.027). Patients with higher education levels exhibited significant cognitive improvement (p = 0.039), while patients with a time since onset of 60–180 days showed a significant decline in cognitive improvement (p = 0.024).ConclusionHigh-frequency rTMS effectively modulated connectivity patterns between the left DLPFC and other brain regions in PSCI patients, enhancing cognitive functions. Changes in wPLI within the theta frequency band may serve as a potential biomarker for cognitive function improvement in PSCI patients. Education level and time since onset may have a certain impact on cognitive improvement in PSCI patients.